Identification of Casz1 as a Regulatory Protein Controlling T Helper Cell Differentiation, Inflammation, and Immunity - Bhaskaran, Natarajan; Liu, Zhihui; Saravanamuthu, Senthil S.; Yan, Chunhua; Hu, Ying; Dong, Lijin; Zelenka, Peggy; Zheng, Lixin; Bletsos, Vassili; Harris, Rachel; Harrington, Brenna; Weinberg, Aaron; et al. (Frontiers in Immunology, 2018)
While T helper (Th) cells play a crucial role in host defense, an imbalance in Th effector subsets due to dysregulation in their differentiation and expansion contribute to inflammatory disorders. Here, we show that Casz1, whose function is previously unknown in CD4+ T cells, coordinates Th differentiation in vitro and in vivo. Casz1 deficiency in CD4+ T cells lowers susceptibility to experimental autoimmune encephalomyelitis, consistent with the reduced frequency of Th17 cells, despite an increase in Th1 cells in mice. Loss of Casz1 in the context of mucosal Candida infection severely impairs Th17 and Treg responses, and lowers the ability of the mice to clear the secondary infection. Importantly, in both the models, absence of Casz1 causes a significant diminution in IFN-γ+IL-17A+ double-positive inflammatory Th17 cells (Th1* cells) in tissues in vivo. Transcriptome analyses of CD4+ T cells lacking Casz1 show a signature consistent with defective Th17 differentiation. With regards to Th17 differentiation, Casz1 limits repressive histone marks and enables acquisition of permissive histone marks at Rorc, Il17a, Ahr, and Runx1 loci. Taken together, these data identify Casz1 as a new Th plasticity regulator having important clinical implications for autoimmune inflammation and mucosal immunity.